Estimates of genetic distance, combining ability and heterosis for body weight of cross four populations of giant gourami, Osphronemus goramy Lacepede 1801 - Sularto Sularto; Rita Febrianti; Suharyanto Suharyanto (Jurnal Iktiologi Indonesia, 2017)
The superior giant gourami can be obtained through hybridization. The purpose of this study was to estimate the genetic distance, combined ability, and crossbreeding heterosis at the age of eleven months from the four gourami populations: Kalimantan, Jambi, Majalengka, and Tasikmalaya. The study was conducted at the Research Institute for Fish Breeding Sukamandi. Genetic distance calculations were done by truss morphometric characterization with a sample of each of crossbred many as 30 individuals with the standard length range 3.5 - 12.2 cm. The data was analyzed using discrimi-nant analysis and continued with "cluster procedure" to get a dendrogram using SAS program 6:03. Heterosis was cal-culated based on the performance of the hybrid compared to the average performance parent each pair consisting of one male and two females. The results of this study showed that the four populations of giant gourami have different genetic distances. Giant gourami population from Borneo have the farthest genetic distance compared with the three other populations, whereas giant gourami from Jambi and from Majalengka has a close genetic distance. Jambi population shows the highest general combining ability with a positive value 21.82 g. The highest value of specific combining ability is obtained from a cross between the Majalengka female with the Jambi male with a positive value 75.30 g. The crosses also has the highest heterosis value that was equal to 41.78%, follows by a cross between the Tasikmalaya fe-male with the Jambi males (30.1%) and a cross between the Borneo females with the Jambi males (22.35%). The three crosses prospectively to produce superior hybrid of giant gourami. Abstrak Hibridisasi merupakan salah satu cara untuk mendapatkan ikan gurami unggul. Penelitian ini bertujuan untuk mengesti-masi jarak genetik empat populasi ikan gurami, yakni : Kalimantan, Jambi, Majalengka, dan Tasikmalaya, serta meng-hitung daya gabung gen serta heterosis persilangannya pada umur 11 bulan. Penelitian dilakukan di Balai Penelitian Pemuliaan Ikan Sukamandi. Perhitungan jarak genetik dilakukan berdasarkan karakterisasi truss morfometrik dengan jumlah sampel masing-masing hasil persilangan sebanyak 30 ekor dengan kisaran panjang baku 3,5 – 12,2 cm. Data dianalisis dengan analisis diskriminan dan dilanjutkan dengan “cluster procedure” untuk mendapatkan dendrogram menggunakan program SAS 6.03. Heterosis dihitung berdasarkan performa hibrida dibandingkan performa rata-rata induk tetuanya masing-masing pasangan induk terdiri atas 1 jantan dan 2 betina. Hasil penelitian ini menunjukkan bahwa keempat populasi ikan gurami mempunyai jarak genetik yang berbeda. Populasi gurami asal Kalimantan mem-punyai jarak genetik terjauh dibandingkan dengan ketiga populasi lainnya, sedangkan ikan gurami asal Jambi dan asal Majalengka memiliki jarak genetik yang dekat. Populasi Jambi menunjukkan daya gabung umum tertinggi dengan nilai positif 21,82 g. Nilai daya gabung spesifik tertinggi didapatkan dari persilangan antara betina Majalengka dengan jantan Jambi dengan nilai positif 75,30 g. Persilangan tersebut juga memiliki nilai heterosis tertinggi yaitu sebesar 41,78%, selanjutnya diikuti persilangan betina Tasikmalaya dengan jantan Jambi sebesar 30,1% dan persilangan betina Kaliman-tan dengan jantan Jambi sebesar 22,35%. Ketiga persilangan tersebut prospektif untuk dijadikan ikan gurami hibrida unggulan.